Effect of halide addition on thermal and elastic properties of binary Li2O-P2O5 glasses. (2022) - Ouachouo, L.; Bih, L.; Jerroudi, M.
Highlights: Elaboration of LiCl-Li2 O-P2 O5 glasses by melt quenched method. Determination of physical properties of glasses such as: density and molar volume. Determination of mechanical properties: hardness and calculating Elastic constants. From the differential thermal analysis, the glass transition temperature (Tg ) of each glass was evaluated. Abstract: Glass issued from the binary Li2 O–P2 O5 are synthesized by the melt quench technique and the effect of alkali-halide, especially lithium chloride, on their thermal and elastic properties is investigated. Other physical and mechanical properties of these glassy materials are determined such as density, molar volume, oxygen packing density, micro-hardness and rigidity. It is observed that the addition of the halide component in the phosphate glass network results in a decrease in its density and molar volume. As well as the glass transition temperature (Tg ) of each glass was determined from the differential thermal analysis. It is recognized that the halide compound affects strongly the viscosity and the dynamic of the glassy-network fragments. The effect of the halide component on the elastic constants of the glasses is also studied by estimating the longitudinal modulus (L), shear modulus (S), Young's modulus (E), bulk modulus (K), and Poisson's ratio values. It can be concluded that all these elastic parameters diminish with increasing the halide content in the chemical composition of the glasses.